Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10815-016-0835-9
|View full text |Cite
|
Sign up to set email alerts
|

The carriers of the A/G-G/G allelic combination of the c.2039 A>G and c.-29 G>A FSH receptor polymorphisms retrieve the highest number of oocytes in IVF/ICSI cycles

Abstract: Purpose The objective of this study was the elucidation of the possible role of the single-nucleotide polymorphisms (SNP) at position -29 and 2039 of the FSH receptor gene (FSHR) as independent predictive markers of ovarian response. Indeed, the tailoring of reproductive treatments is crucial for both maximizing the success of IVF patients and obtaining a reduction in hypo-or hyper-response rates. Methods This prospective, observational study analyzed the association of -29 and 2039 FSHR polymorphisms with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…FSHR :c.919G>A and FSHR :c.2039G>A were previously associated with variability in serum FSH levels and reproductive outcomes in different populations ( 11 13 , 15 , 30 34 ). These SNVs are located in the coding region of the FSHR gene and have been well characterized ( 13 ).…”
Section: Discussionmentioning
confidence: 86%
“…FSHR :c.919G>A and FSHR :c.2039G>A were previously associated with variability in serum FSH levels and reproductive outcomes in different populations ( 11 13 , 15 , 30 34 ). These SNVs are located in the coding region of the FSHR gene and have been well characterized ( 13 ).…”
Section: Discussionmentioning
confidence: 86%
“…In a number of studies, rs6166 showed an association with basal FSH levels, the time required for stimulation [ 21 - 23 , 28 , 30 ], the number of retrieved oocytes [ 4 , 28 , 29 , 32 , 39 ], and implantation and pregnancy rates [ 40 ]. On the contrary, in other studies, rs6166 was reported to have no association with ovarian response, especially oocyte retrieval, pregnancy rate, and FSH levels [ 24 , 34 , 41 ]. The results of the present study are consistent with the findings of the majority of previous studies regarding the important role of this SNP in determining the response of women to ovarian stimulation.…”
Section: Discussionmentioning
confidence: 79%
“…51 In a similar study in a Greek population, ESR1 Pvu II CC/AA genotypes and FSHR Ser680Asn polymorphisms were the worst, while the combination of TC/SA was the most favorable for achieving pregnancy after IVF. 102 A recent study has also shown that women homozygous for the serine amino acid (S) of both LHCGR Asn312Ser and FSHR Asn680Ser polymorphisms had an increased probability of pregnancy in IVF cycles, 103 while in another study women with the combination of A/G-G/G of c.2039A>G and c.-29G>A FSHR polymorphisms produced an increased number of oocytes after COS. 104 Of particular interest is also the possible interaction between polymorphisms in the AMH and FSHR genes in relation to the number of the mature oocytes produced. 50…”
Section: Gene Polymorphisms and Ovarian Response Following Controlled Ovarian Stimulationmentioning
confidence: 99%